(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article examines Seyla Benhabib’s contribution to debates on multiculturalism, recognition, and redistribution, arguing that her attempt to reconcile liberal egalitarianism with Hegelian critical theory remains philosophically incomplete. While Benhabib successfully distinguishes individual authenticity from collective cultural recognition and defends democratic protections for individuals within minority groups, the commentary argues that she ultimately avoids the dialectical implications of this distinction. Rather than treating the tension between individual and collective identity as a constitutive form of Hegelian negativity, Benhabib seeks to contain it within the existing framework of liberal democracy. The article further criticizes her failure to extend her analysis toward a more radical critique of capitalism, the nation-state, and the historical transformations produced by migration and globalization. Although Benhabib offers a sophisticated critique of cultural essentialism and multicultural politics, her reliance on liberal-democratic institutions prevents her from fully embracing the Marxist-Hegelian conception of contradiction, conflict, and historical transformation. The article concludes that a genuinely dialectical theory of recognition requires not only redistribution and recognition but also a critical interrogation of the social and economic structures that generate cultural conflicts themselves. This abstract is generated with artificial intelligence.